Impact of 68Ga-FAPI PET/CT imaging on the therapeutic management of primary and recurrent pancreatic ductal adenocarcinomas - Röhrich, Manuel; Naumann, Patrick; Giesel, Frederik L.; Choyke, Peter L.; Staudinger, Fabian; Wefers, Annika K.; Liew, Dawn P.; Kratochwil, Clemens; Rathke, Hendrik; Liermann, Jakob; Herfarth, Klaus; Jäger, Dirk; et al. (Journal of nuclear medicine, 2021)
Pancreatic ductal carcinoma (PDAC) is a highly lethal cancer, and early detection and accurate staging are critical to prolonging survival. PDAC typically has a prominent stroma including cancer-associated fibroblasts that express fibroblast activation protein (FAP). FAP is a new target molecule for PET imaging of various tumors. In this retrospective study, we describe the clinical impact of PET/CT imaging using 68Ga-labeled FAP-inhibitors (68Ga-FAPI PET/CT) in 19 patients with PDAC (7 primary, 12 progressive/recurrent).